Viral Infections and Associated Factors That Promote Acute Exacerbations of Asthma - Kim, Chang-Keun (Allergy Asthma Immunol Res, 2018)
Despite asthma being the most common chronic childhood ailment, there is still much to learn about the disease. Early childhood infections with well-known or emerging viruses can lay the pathophysiologic framework for asthma development and exacerbation later in life, which may be due partly to alteration of the airway microbiome. Once asthma is established, acute exacerbations are usually associated with infections with respiratory viruses, such as rhinoviruses (RVs). Once again, there are bidirectional interactions between viruses and airway bacteria that appear to influence the severity of illness and the likelihood of exacerbation. Studies employing recent advances in viral and bacterial identification analytic techniques will clarify these new concepts and may provide the basis for new treatments or prevention or respiratory infection-associated exacerbation. This paper is a review of the associations among respiratory viruses, bacteria, inflammatory mechanisms, and asthma exacerbation.